Analysis of the economic value of Matanaga Farm agrotourism - Khaswarina, Shorea -; Herlon, Meki; Ridho, Zulhamid; Phreti, Phreti (Department of Agribusiness, Faculty of Agriculture, Universitas Trunojoyo Madura, Indonesi, 2024)
Matanaga Farm Agrotourism is a tourist destination that offers a fruitful tourist concept. The demand for tourism will rise as travel costs are minimized by visitors. This research is aimed at analyzing and estimating the economic value of Agrowisata Matanaga Farm. The method of research is the method of analysis of travel cost method. The results of the study obtained a consumer surplus of visitors to Agrowissata Matenaga Farm amounting to IDR381.659 per person per one visit, so processed the economy value of Agrowisat Matanega Farm amounted to IDR829.345.007/year.